2013
DOI: 10.1155/2013/572954
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term (1951–2007) Rainfall Trends around Six Indian Cities: Current State, Meteorological, and Urban Dynamics

Abstract: The present study focuses on analyzing the precipitation trends over six Indian cities during the summer monsoon (June–September) covering the period 1951–2007 and also attempting to investigate possible urban forcing and dynamics by examining the variation in precipitation in the upwind and downwind directions. The analysis shows negative trends in the total number of rainy days over Hyderabad (−10.4%), Kanpur (−7.1%), Jaipur (−10.5%), and Nagpur (−4.8%) and positive trends over Delhi (7.4%) and Bangalore (22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…The APHRODITE has a spatial resolution of 0.25 × 0.25 and is found to be a better performing rainfall dataset for Peninsular Malaysia than other rainfall data products (Tan et al, 2015). APHRODITE has a daily rainfall record for 57 years and therefore it is often recommended for the assessment of long-term trend in rainfall (Yatagai et al, 2012;Kharol et al, 2013;El Kenawy et al, 2016;Kishore et al, 2016;Soraisam et al, 2018). The location of APHRODITE grid points (total 178) on the map of Peninsular Malaysia is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The APHRODITE has a spatial resolution of 0.25 × 0.25 and is found to be a better performing rainfall dataset for Peninsular Malaysia than other rainfall data products (Tan et al, 2015). APHRODITE has a daily rainfall record for 57 years and therefore it is often recommended for the assessment of long-term trend in rainfall (Yatagai et al, 2012;Kharol et al, 2013;El Kenawy et al, 2016;Kishore et al, 2016;Soraisam et al, 2018). The location of APHRODITE grid points (total 178) on the map of Peninsular Malaysia is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Singh et al [] it has been shown that extreme wet and dry spells during the ISM have statistically significant changes in their intensity and frequency in the period between 1951 and 2011. Also, it has been suggested that the ISM is showing two contrasting phases: a wetter early summer followed by a drier period, with a possible influence of aerosol concentrations on precipitation patterns [ Gautam et al , ; Kharol et al , ].These changing rainfall patterns have been hypothesized to lead to an increased risk of droughts [ Mishra and Liu , ]. See Text S1 in the supporting information (SI) for further detailed discussion on ISM and climate change.…”
Section: Introductionmentioning
confidence: 99%
“…edu/, accessed on 15 March 2023) (Table 1). Urban-land expansion is presented as an urban area percentage, which refers to the ratio between the urban and total land areas, serving as a measure of the degree of urbanization [60].…”
Section: Key Driving Factorsmentioning
confidence: 99%